Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ù„Ø¨Ø© Ø¹Ù„Ù‰ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¹Ø§Ù„Ù‰ Ø§Ù„ØªØ±Ø¨ÙˆÙŠ Ø§Ù„Ù‡Ù„Ø§Ù„ Ø³Ø¬Ù„ÙŠ - Teuku Sanwil (Jurnal Pendidikan dan Pengajaran, 2023)
This study aims to determine the students' ability to read Arabic texts between graduates of general high schools and Islamic high schools, as well as to identify the differences in the students' ability to read Arabic texts between graduates of general high schools and Islamic high schools. Additionally, it aims to ascertain the factors influencing students' ability to read Arabic texts among graduates of general high schools and Islamic high schools. The research methodology employed by the researcher in this study is the descriptive-analytical method. The research tools utilized for data collection include observation, personal interviews, tests, documents, and questionnaires.The research results indicate that the students' ability to read Arabic texts is high. This is evident from the average score obtained by students from general high schools, denoted as variable 'x,' which is 81.25, corresponding to the "very good" level of proficiency. On the other hand, the average score attained by students from Islamic high schools, denoted as variable 'y,' is 95, equivalent to the "excellent" level of proficiency, although some of them still have lower scores. The difference between the two groups in reading Arabic texts is not substantial, as indicated by a Pearson correlation coefficient of 0.811 and a Spearman correlation coefficient of 0.44. The researcher concludes that there is a significant relationship between graduates of general high schools and Islamic high schools regarding their ability to read Arabic texts, based on the calculated correlation of 0.44rxy.Factors affecting students' ability to read Arabic texts among graduates of general high schools and Islamic high schools encompass educational background, utilizing leisure time for learning Arabic texts, exerting substantial effort to comprehend them, seeking assistance from friends for unclear matters, enhancing study habits, and showing interest in Arabic texts.